Relação entre funcionalidade e satisfação em pacientes acometidos por acidente vascular encefálico: o uso da reabilitação cognitiva por meio das atividades de vida diária e atividades instrumentais de vida diária - FAZZI, Graziela Cabral (2023)
Introduction: The stroke compromises the function of the affected brain areas, affecting sensorimotor, cognitive and behavioral functions, resulting in deficits that compromise the functionality, interfering in occupations and can have a negative influence on the individual's satisfaction and participation in achieving ADL's and IADL's. Objective: To understand the relationship between functionality and satisfaction in performing ADLs and IADL's in patients affected by stroke, through the cognitive rehabilitation approach. Methodology: The study is characterized as a longitudinal study of pre and post intervention, qualitative nature through single case study, affected patient by stroke, the sessions were performed in outpatient and at home, for the period from May to August 2016 by setting up in 17 visits, data collection was performed at the beginning and end of the study, through KATZ protocols, MIF, COPM and through registration of changes in order to measure the functionality and evaluate satisfaction of individuals in performing ADLs and IADL's. Results: KATZ index at baseline showed dependence requiring human assistance in ADLs dressing, feeding and transfer, and revaluation found independence in all ADLs. The MIF presented the modified dependency initial assessment and reassessment scored as full or modified independence. The COPM presented in changing score 25 points in performance and satisfaction 29 points. The records of developments corroborate the results of the protocols. Discussion: The results showed significant improvement in functionality and satisfaction of ADLs and IADL's, with relationship between them, and revealed by the results of the protocols and through analysis of the evolutions of the sessions. Conclusion: This way the functionality and satisfaction have an intrinsic relationship in cognitive rehabilitation process focusing on ADLs and IADL's, in patients affected by stroke, there by contributing to improving the quality of life of patients.